PENELITIAN PERAN PUSTAKAWAN DALAM LITERASI BACA DAN TULIS BAGI ANAK PENYANDANG DISABILITAS (TUNA RUNGU) MELALUI DATABESE GOOGLE SCHOLAR : NARRATIVE LITERATURE REVIEW - Fadilla, Nurul; Anwar, Rully Khairul; Rukmana, Evi Nursanti; Djen Amar, Siti Chaerani (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2024)
Abstract : Librarians as employees of the State's national apparatus, have duties as planners, executors and supervisors of the implementation of tasks in providing services to the community. This also applies to persons with disabilities, that they also have the right to receive information, to be able to interpret things that may be difficult for them to understand. Librarians must also have high creativity, because they must be creative in conveying basic literacy for persons with disabilities. If it goes well, the purpose of the library in providing services to the community can certainly be achieved. This study uses the literature study method, analyzes previous research topics, then presents a new theory and is different from previous research, but still related to previous research. The data used in this paper is the result of previous research that has been published in various online journals both nationally and internationally. This data collection is carried out by selecting the source of information needed by the author in each journal which is taken according to predetermined criteria. These criteria include, the year of the source of the information, ranging from 2013 to 2023. As for the purpose of this study, researchers want to find out what the role of librarians is in reading and writing literacy to convey to children with disabilities.